2018
DOI: 10.1002/jcb.26609
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐6803‐5p as potential diagnostic and prognostic marker in colorectal cancer

Abstract: Accumulating data have suggested exosome-delivered microRNAs (miRNAs) play critical role in carcinogenesis and cancer progression. However, little is known about the influence of exosomal miR-6803-5p on the development and prognosis of colorectal cancer (CRC). Levels of serum exosomal miR-6803-5p were determined by microarray analysis and verified by quantitative real-time PCR (qRT-PCR). Outcomes of overall survival (OS) and disease-free survival (DFS) of CRC patients were estimated by Kaplan-Meier analysis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 29 publications
2
57
0
1
Order By: Relevance
“…Serum extracellular miR-150-5p has been confirmed as an independent prognostic indicator of CRC, and the survival time of patients with a low expression of serum extracellular miR-150-5p was significantly longer than that of patients with high expression [134]. Similar results were obtained in serum, where high levels of exosomal miR-6803-5p have been shown to be associated with the poor prognosis of CRC [135]. Another study revealed that, compared with healthy individuals in the control group, the expression levels of miR-19a and miR-92a in the serum of patients with CRC are significantly increased, which is associated with CRC recurrence [136].…”
Section: Emerging Liquid Biopsy Markerssupporting
confidence: 55%
“…Serum extracellular miR-150-5p has been confirmed as an independent prognostic indicator of CRC, and the survival time of patients with a low expression of serum extracellular miR-150-5p was significantly longer than that of patients with high expression [134]. Similar results were obtained in serum, where high levels of exosomal miR-6803-5p have been shown to be associated with the poor prognosis of CRC [135]. Another study revealed that, compared with healthy individuals in the control group, the expression levels of miR-19a and miR-92a in the serum of patients with CRC are significantly increased, which is associated with CRC recurrence [136].…”
Section: Emerging Liquid Biopsy Markerssupporting
confidence: 55%
“…Some other predicted target miRNAs of hsa_circ_0000109 , including miR‐637 , miR‐3620‐5p , miR‐3064‐5p , and miR‐6803‐5p , have not been reported directly related to functional regulations of HUVECs. But these miRNAs have been unveiled to play central roles in the competing endogenous RNA (ceRNA) network in others diseases . However, they might be new targets in ceRNA network in vascular endothelium damage caused by high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent evidence has suggested that liver pre-metastatic niche could be promoted by exosomal miR-21 of CRC cells, through the miR-21-TLR7-IL6 axis [116]. Significantly increased levels of serum exosomal miR-6803-5p [117] and decreased levels of miR-548c-5p have been recently associated with poor survival and liver metastasis of CRC patients [118]. However, the molecular mechanisms by which both miR-6803-5p and miR-548c-5p influence CRC metastasis remain largely unknown.…”
Section: The Role Of Mirnas -Tex In Sustaining the Crc Liver Metastasismentioning
confidence: 99%